Evaluating elastic-plastic behaviour of rock materials using hoek–brown failure criterion - Hasanzadehshooiili, Hadi; Lakirouhani, Ali; Medzvieckas, Jurgis (Journal of Civil Engineering and Management, 2012)
As a matter of fact, the failure criteria only predict failure’s initiation in materials. And, in order to predict post-yield behaviour of materials, a much complicated formulation for stress-strain relationship is required, which we know as plasticity theory. For instance, these formulations are developed based on Mohr-Coulomb criterion for soils and Drucker-Prager criterion for concrete. According to a majority of rock mechanics researchers, the empirical and experimental Hoek-Brown failure criterion is one of the well-progressed and suitable criteria, which can efficiently predict the rock failure initiation under different stress states for various types of intact rocks and rock masses. In this article, according to the suggestion by Heok explained in his paper of 1997, this rugged mentioned criterion is considered as a yield criterion and the elastic-perfect plastic behaviour of rock masses is determined using calculating material constitutive matrix’s arrays in terms of Hoek-Brown’s material constants and mechanical characteristics of rock materials in the general stress space, considering associated flow rule.